2016
DOI: 10.1161/circinterventions.114.002356
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Replacement of Stenotic Aortic Valve Normalizes Cardiac–Coronary Interaction by Restoration of Systolic Coronary Flow Dynamics as Assessed by Wave Intensity Analysis

Abstract: Background-Aortic valve stenosis (AS) can cause angina despite unobstructed coronary arteries, which may be related to increased compression of the intramural microcirculation, especially at the subendocardium. We assessed coronary wave intensity and phasic flow velocity patterns to unravel changes in cardiac-coronary interaction because of transcatheter aortic valve implantation (TAVI). Methods and Results-Intracoronary pressure and flow velocity were measured at rest and maximal hyperemia in undiseased vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…11 At wave intensity analysis, the microcirculatory decompression (suction) was found to decrease and the forward compression wave to increase after TAVI, reflecting the reduction in myocardial work required to eject blood past a stenosed aortic valve and the immediate improvement in the coronary physiological reserve induced by the aortic valve replacement. 11,12,29 TAVI, inducing an immediate decrease in hyperemic microvascular resistance and an increase in hyperemic flow velocity, is associated with an immediate improvement in the reserve vasodilator capacity of the coronary microcirculation. 10 Increased extravascular compression and reduced diastolic perfusion time, rather than vascular remodeling, influence coronary microvascular dysfunction in AVS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 At wave intensity analysis, the microcirculatory decompression (suction) was found to decrease and the forward compression wave to increase after TAVI, reflecting the reduction in myocardial work required to eject blood past a stenosed aortic valve and the immediate improvement in the coronary physiological reserve induced by the aortic valve replacement. 11,12,29 TAVI, inducing an immediate decrease in hyperemic microvascular resistance and an increase in hyperemic flow velocity, is associated with an immediate improvement in the reserve vasodilator capacity of the coronary microcirculation. 10 Increased extravascular compression and reduced diastolic perfusion time, rather than vascular remodeling, influence coronary microvascular dysfunction in AVS.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] TAVI has been demonstrated to exert an immediate effect on coronary flow, 10 and recently, the immediate improvement in the coronary physiological reserve induced by the aortic valve replacement has been demonstrated using wave intensity analysis. 11,12 However, little is known about the functional effects of the pressure overload on coronary stenosis and if, and to which extent, the removal of the outflow obstruction may influence the relation between coronary stenosis and FFR in severe AVS.…”
mentioning
confidence: 99%
“…One of the important factors contributing to CMC in HCM is related to "contraction-coronary coupling" as shown by wave intensity analysis (11) (Figure 8). This type of CMC is markedly aggravated by LVOTO and is expected to improve immediately after relief of LVOTO in a manner similar to that observed after relief of aortic stenosis (12). Further improvement in the coronary microcirculation after relief of LVOTO can occur due to reverse myocardial remodeling, which occurs after myectomy (13).…”
Section: The Coronary Circulationmentioning
confidence: 81%
“…Previous work has demonstrated that both LVH 9 and the presence of an outflow tract obstruction 10,12 have individual effects on coronary WIA. In this study, we have identified and separated these contrasting effects within individual patients with severe aortic stenosis and as such have shown that three states exist: With intervention, there is no immediate change in LV mass index (A).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ventricular remodelling may even confound some studies where a follow-up measure is performed outside of the immediate peri-operative setting as the most rapid hypertrophy regression occurs largely within the first 6 months. 10,12 Furthermore, in patients without significant valvular disease, LVH results in a relative reduction in the BDW reflecting a disruption in ventricular-coronary interaction. It has proven able to document the potentially opposing influences of LVH 9 and aortic stenosis 10 on coronary physiology where abnormalities can be appreciated in the backward decompression wave (BDW).…”
Section: Introductionmentioning
confidence: 99%